A Novel Bispecific Antibody Targeting PD-L1 and VEGF With Combined Anti-Tumor Activities - Xiaopei Cui (Frontiers Media S.A., 2021)
Therapeutic monoclonal antibodies (mAbs) blocking immune checkpoints have been mainly used as monotherapy. Recently, combination therapy targeting multiple immune checkpoints has recently been explored to increase anti-cancer efficacy. Particularly, a single molecule targeting more than one checkpoints has been investigated. As dual blocking of PD-1/PD-L1 and VEGF/VEGFR has demonstrated synergism in anti-tumor activities, we developed a novel bispecific antibody, termed HB0025, which is formed via fusing the domain 2 of vascular endothelial growth factor receptor 1 (VEGFR1D2) and anti-PD-L1 mAb by using mAb-Trap technology. HB0025 almost completely retains the binding affinities and the biological activities in-vitro when compared with the parent anti-PD-L1 mAb or VEGFR1D2 fusion protein. Preclinical data demonstrated that HB0025 was more effective in inhibiting cancer growth than anti PD-L1 mAb or VEGFR1D2 fusion protein. Thus, our bispecific antibody may bring about greater clinical benefits and broader indications.